Determination of acrylamide in fried starchy foods by gas chromatography-mass spectrometry - Zhong, Weike; Chen, Dongdong; Yong, Wei; Liu, Zhiming; Qiu, Yueming; Tang, Yingzhang (Sepu, 2005)
A method was developed for the determination of acrylamide in fried starchy foods using isotope dilution gas chromatograpy-selected mass spectrometry (GC-MS). The acrylamide was extracted from samples by water, then centrifuged and cleaned up by a column of graphitized carbon black. Acrylamide was derivatized through bromination at low pH and low temperature and determined by GC-MS. With the aid of the 13C-substituted acrylamide internal standard, the mass spectrum in GC-MS was interpreted, and the content of acrylamide was measured. The limit of quantitative detection (S/N > 10) was 5 microg/kg and the recovery was in the range of 90%-105% and relative standard deviation is 6.3%. The levels of acrylamide in some fried foodstuffs such as French fries was surveyed using the method. French fries were found to contain 278-4518 microg/kg acrylamide. It means that the content of acrylamide in French fries is 10,000 times higher than the drinking water guideline of World Health Organization for acrylamide.